The dawn phenomenon is related to overnight growth hormone release in adolescent diabetics. - Edge, J; Matthews, DR; Dunger, D (1990)
We have investigated the relation between nocturnal insulin requirements and nocturnal growth hormone (GH) release in 26 diabetic adolescents at various puberty stages and have examined the effect of nocturnal GH suppression on pre-breakfast insulin requirement. In all the studies, euglycaemia was maintained overnight using a computer-calculated variable-rate insulin infusion, and 15-min blood samples were collected for GH assay. During initial clamp studies, insulin infusion rates were greater from 0500-0800 h (15.22 +/- 0.95 mU/kg/h, mean +/- SEM) than from 0100-0400 h (12.42 +/- 0.84 mU/kg/h, P less than 0.001). The increase in insulin infusion rate correlated with mean overnight GH concentration (r = 0.68, P less than 0.001), and was maximal at puberty stage 3 in both sexes. In seven of the subjects, a second identical clamp was performed following administration of 100 mg oral pirenzepine. During these studies, mean overnight GH levels were reduced by 11-85%, from 17.6 +/- 1.6 to 7.5 +/- 2.2 mU/l; P less than 0.01. Insulin requirements were not significantly different between the periods 0100-0400 and 0500-0800 h during these studies, and the reduction in pre-breakfast (0500-0800 h) insulin requirement when compared with the baseline studies correlated with the fall in GH secretion (rs = 0.82, P less than 0.01). The dawn increase in insulin requirement in adolescents with IDDM is related to the overnight GH secretion during puberty, and pre-breakfast insulin requirement can be reduced by suppressing nocturnal GH release.